Effects of dietary L-Ascorbyl-2-Polyphosphate as a source of vitamin C on growth indices in beluga sturgeon (Huso huso L.) - Soltani, M.; Falahatkar, B.; Pourkazemi, M.; Abtahi, B.; Kalbassi, M.R.; Mohseni, M. (2008)
Six diets supplemented with 0, 100, 200, 400, 800, and 1600mg/kg L-Ascorbyl-2-Polyphosphate (APP) as vitamin C, were fed to juvenile beluga sturgeon in three replicates for 16 weeks. Fifty five fish with an average weight 38.1 plus or minus 0.5 g were distributed to each tank after adaptation to the experimental diets. Most of the growth performance indices at week 4 indicated significant differences (P<0.05), except in CF and PER (P<0.05). The survival was affected by dietary treatment at week 4 (P<0.05). No deficiency sign was observed during the trial. Results of this study indicated that vitamin C can have remarkable effects on growth indices in different growth periods. Therefore, regarding the effects of vitamin C on the growth indices and in the fish weight range used in this study, 100-200 mg/kg vitamin C (APP) can be considered as the optimum level for rearing the fish.